Expression profiles of XIK1 and OsSWEET14 genes in parental and back‐ crossing rice lines after Xanthomonas oryzae pv. oryzae infection - Atirada Boondech; Kawee Sujipuli; Kumrop Ratanasut; Tepsuda Rungrat; Thanita Boonsangsrom; Niran Aeksiri; Wittaya Tawong; Pongsanat Pongcharoen (Indonesian Journal of Biotechnology, 2024)
Oryza sativa L. ssp. indica (RD47 cultivar) is a major commercial rice variety known for its highly stable yields. However, it is highly susceptible to bacterial blight disease caused by Xanthomonas oryzae pv. oryzae (Xoo). While previous research has focused on improving rice cultivars through breeding programs, no reports involved the interaction between Xoo infection and gene expression. This study aimed to analyze the relationship between bacterial blight disease and gene expression, focusing on two resistance genes (Xa21 and XIK1) and one susceptible gene (OsSWEET14). Gene expression analysis revealed that the Xa21 gene conferred effective resistance against bacterial blight Xoo16PK002 infection, providing high and moderate resistance to bacterial blight symptoms in two rice varieties carrying the Xa21 gene, IRBB21 and the near–isogenic RD47–Xa21 BC4F4, respectively. Additionally, the Xa21 gene directly induced XIK1 expression in both resistance rice cultivars. Moreover, one susceptible gene, OsSWEET14, was consistently up–regulated in only the bacterial blight–susceptible indica rice cultivar RD47. Therefore, the up–regulation of resistance genes and the suppression of susceptible genes contributed to the improvement of bacterial blight disease in the RD47 cultivar. Xa21 emerged as a criti‐ cally important gene in directly inducing mechanisms against Xoo, thereby promoting the reduction of bacterial blight disease.